From “the Miraculous as Real” to “the Real as Miraculous”: On Evolution of Arab Travelogue in the 19th Century - Alexander B. Kudelin (Studia Litterarum, 2024)
The rise of the New Arabic literature was highlighted by the publication of several 19th-century travelogues by Egyptian authors: “The Extrication of Gold in Summarizing Paris” by al-Ṭahṭāwī, “The Sheikh’s Journey to The Russian Country” by al-Ṭanṭāwī, and “‛Alam al-dīn” by Mubārak. The celebration of the achievements of European technical progress and civilization in these works reveals their genetic closeness to the medieval genre of riḥla (Arab. “travel”), which unites the scientific and the artistic, balancing between the factual and the fictitious. In the New Arabic literature, travelogues are seen as offering simultaneously a continuation of medieval works of riḥla and a contrast to them. Both groups of Arabic works, medieval and new-Arabic, served to expand the horizon of compatriot readers through descriptions of uncommon phenomena that transgress the limits of their accustomed reality. The principal difference between the two groups of texts comes down to the following: the medieval works treat the miraculous (ʽadjā’ib, mirabilia) as an integral part of the real-world outlook of a medieval Arab Muslim, whereas in the writings of the Arab enlighteners, the miraculous is perceived as strange and outlandish and something having to do with the realities of foreign lands, alien to the Arab-Muslim world, which used to be almost intact, but in the 19th century opened up to many renewals from the outer world.